2011
DOI: 10.3109/15563650.2011.584879
|View full text |Cite
|
Sign up to set email alerts
|

The combination of cobinamide and sulfanegen is highly effective in mouse models of cyanide poisoning

Abstract: SUMMARY Context Cyanide poisoning is a major contributor to death in smoke inhalation victims and accidental exposure to cyanide occurs in a variety of industries. Moreover, cyanide has the potential to be used by terrorists, particularly in a closed space such as an airport or train station. Current therapies for cyanide poisoning must be given by intravenous administration, limiting their use in treating mass casualties. Objective We are developing two new cyanide antidotes—cobinamide, a vitamin B12 analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…Since no nitrite was present in these experiments, and we have previously shown that sulfite has no antidotal effect against cyanide, we conclude that thiosulfate augments cobinamide. 25 …”
Section: Resultsmentioning
confidence: 99%
“…Since no nitrite was present in these experiments, and we have previously shown that sulfite has no antidotal effect against cyanide, we conclude that thiosulfate augments cobinamide. 25 …”
Section: Resultsmentioning
confidence: 99%
“…[14] Cobinamide (Cbi, Figure 1b) is a cobalamin derivative lacking DMBI moiety. Recently this compound has attracted researchers' interests due to the high efficacy of its derivatives as cyanide antidotes (sulfitocobinamide) [15][16][17] and cyanide chemosensors (monocyanocobinamide). [18][19][20] Cbi application is also of interest in the study of both Co 3+ → Co 2+ and Co…”
Section: Introductionmentioning
confidence: 99%
“…Our goal was to rigorously assess if sodium nitrite and sodium thiosulfate are effective when administered by intramuscular injection by testing them in three well-established lethal mammalian models of cyanide poisoning: ( i ) a mouse model of inhalational cyanide exposure that simulates a scenario of gaseous cyanide poisoning (8;10;11); ( ii ) a rabbit model where severe hypotension is the trigger for treatment (9;12;13), and ( iii ) a pig model where apnea is the trigger for treatment (14-16). …”
Section: Introductionmentioning
confidence: 99%